Place-making and performance: The impact of walkable built environments on business performance in Phoenix and Boston. (February 2019) - Credit, Kevin; Mack, Elizabeth
This paper examines the importance of place-making in economic development by evaluating the relationship between specific urban design features – based on Jacobs' "four generators of diversity" and Ewing and Cervero's "Five-D's" – and business sales volume. Despite the increased recognition of the importance of walkable urbanism in recent years, relatively little research has assessed the potential economic development benefits of walkable places. While a few authors have assessed the impact of urban design on property values, this paper fills a gap by examining links between components of walkable built environments and individual business characteristics. This paper uses a Hierarchical Linear Modeling framework to explicitly look at the relationship between neighborhood built environment features at the Census tract level and the sales volume per employee of individual businesses in 2010. The cities of Phoenix and Boston are used as contrasting study sites in order to inspect how larger regional characteristics influence the built environment–performance link. The results indicate that specific features of walkable built environments are positively associated with business performance. However, the relationship between walkable built environments and business performance varies considerably depending on the type of business and city-level context being studied, indicating that significant nuance must be used when considering place-based economic interventions. Although no causal statements can be made about the built environment and business performance, the results of this paper indicate that (in some contexts) design-based place-making initiatives could be used to generate sustainable local economic development.